Efficacy and safety of pembrolizumab in patients with advanced endometrial cancer: a systematic review and meta-analysis - Pan, Biqiong; Lai, Xiaojun; Lu, Jiefang; Bao, Xiaoyan; Fan, Zengke; Sun, Jie (Frontiers in Oncology, 2025)
ObjectiveThis meta-analysis evaluated pembrolizumab monotherapy and combination therapy’s efficacy and safety in recurrent or advanced endometrial cancer (EC).MethodsWe utilized PubMed, Embase, Cochrane Library, and Web of Science databases to identify clinical trials that were used to search literature from July 2013 to July 2023 to evaluate the efficacy and safety of pembrolizumab in patients with advanced EC. Eight studies with 2,742 patients were included. Outcomes were progression-free survival (PFS), overall survival (OS), objective response rate (ORR), complete remission (CR), and adverse events (AEs); a subgroup analysis was carried out based on combination treatment regimens. Quality assessment of the included studies was conducted using the Cochrane Risk of Bias Tool, the Newcastle–Ottawa Scale (NOS), and the Joanna Briggs Institute (JBI) critical appraisal checklist.ResultsPembrolizumab reduced progression risk [hazard ratio (HR): 0.53; 95% confidence interval (CI): 0.44, 0.63; p < 0.00001] and death risk when combined with lenvatinib (HR: 0.67; 95% CI: 0.59, 0.76; p < 0.00001). Pembrolizumab monotherapy and lenvatinib combination achieved higher ORR (OR: 3.61; 95% CI: 2.12, 6.13; p < 0.00001) and CR rates (OR: 2.7; 95% CI: 1.59, 4.57; p < 0.05) than controls. Single-arm studies: 8% CR and 4% PR in pembrolizumab-treated patients. Pooled AE incidence: 86%, with 43% grade 3/4. Two randomized controlled trials (RCTs) found that the pembrolizumab group had a higher incidence of grade 3 or 4 AEs compared to the control group (OR: 2.23; 95% CI: 1.23, 4.04; p = 0.008).ConclusionPembrolizumab monotherapy or combination significantly improves survival in recurrent or advanced EC and has manageable toxicity albeit with a relatively high incidence of treatment-related AEs.